Low‐grade albuminuria associated with brachial‐ankle pulse wave velocity in young adults with type 2 diabetes mellitus in China. Issue 3 (18th October 2014) - Huang, Lingning; Yang, Liyong; Zhang, Songjing; Liu, Donghui; Yan, Xiaofang; Yan, Sunjie
Abstract Background Cardiovascular disease is prevalent in type 2 diabetics, and microalbuminuria is associated with cardiovascular disease morbidity. We aimed to investigate the potential association between low‐grade albuminuria and arterial stiffness in patients with type 2 diabetes. Methods Between 2009 and 2013, a retrospective study was performed in 578 patients with type 2 diabetes (339 male patients and 239 female patients) with normal urinary albumin‐to‐creatinine ratios (ACRs; <30 mg/g) from Fuzhou, China. Patients were stratified into tertiles based on urinary ACR levels (lowest tertile, urinary ACR < 4.8 mg/g; highest tertile, urinary ACR ≥ 20.1 mg/g). Arterial stiffness was measured via brachial‐ankle pulse wave velocity. Results Brachial‐ankle pulse wave velocity, age, duration of diabetes, systolic blood pressure and pulse wave velocity progressively increased across all urinary albumin‐to‐creatinine ratio tertiles (p < 0.05). Patients in the second and the highest tertiles had significantly elevated pulse wave velocity [114.6 mm/s (95% CI = 36.8–192.4) and 209.4 mm/s (95% CI = 131.8–286.9)], p = 0.004 and 0.000] compared with those in the lowest ACR tertile. The association between ACR and elevated pulse wave velocity still persisted in patients younger than 65 years of age and those with diabetes <10 years, conferring 45 or 51% greater risk of elevated pulse wave velocity (OR = 1.451; 95% CI = 1.119–1.881; p = 0.005 or OR = 1.515; 95% CI = 1.167–1.966; p = 0.0018) with each ACR tertile increment. Each ACR tertile increment conferred 31.7% higher risk of increased pulse wave velocity (OR = 1.317; 95% CI = 1.004–1.729; p = 0.0468). Conclusions Patients with type 2 diabetes with urinary albumin excretion in the upper normal range were still at risk for target organ damage. Low‐grade albuminuria might be an early marker for the detection of arterial stiffness in patients with type 2 diabetes, especially in younger patients with type 2 diabetes with shorter durations of disease. Copyright © 2014 John Wiley & Sons, Ltd.